2016
DOI: 10.1597/15-071
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Consensus in the Measurement of Psychological Adjustment to Cleft Lip and/or Palate

Abstract: To date, these measures have been implemented within a UK-wide longitudinal cohort study (at diagnosis, 18 months, 3 years, 5 years, and 8 years) and adopted into the national routine clinical audit protocol for cleft lip/palate at age 5. Further data collection points will follow as the cohorts age. Over time, consistency in data collection will allow researchers to address some of the key unanswered questions in relation to psychological adjustment to cleft lip/palate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 17 publications
1
32
0
Order By: Relevance
“…Such an initiative would be a major undertaking, requiring a culture change among researchers, clinicians, and patients alike—but it can be done. In the United Kingdom, an agreement has been achieved between a team of researchers and all of the professional groups that deliver care for patients with cleft lip/palate on a common set of measures that are administered at key stages of development in a prospective birth cohort study (Stock et al, 2016). In a separate initiative, a globally agreed-upon approach to patient outcome measures in cleft care has been reached by an international task force (International Confederation for Cleft Lip and Palate and Related Craniofacial Anomalies, 2017).…”
Section: Moving Forward: a Route Map To Underpin Healthcare That Bettmentioning
confidence: 99%
“…Such an initiative would be a major undertaking, requiring a culture change among researchers, clinicians, and patients alike—but it can be done. In the United Kingdom, an agreement has been achieved between a team of researchers and all of the professional groups that deliver care for patients with cleft lip/palate on a common set of measures that are administered at key stages of development in a prospective birth cohort study (Stock et al, 2016). In a separate initiative, a globally agreed-upon approach to patient outcome measures in cleft care has been reached by an international task force (International Confederation for Cleft Lip and Palate and Related Craniofacial Anomalies, 2017).…”
Section: Moving Forward: a Route Map To Underpin Healthcare That Bettmentioning
confidence: 99%
“…21 For example, a 2015 study found that more than 60 different measures were being used to evaluate children’s ability to socially adjust to CL/P. 22 Recently, great attention has been paid to developing standardized clinician-reported and patient-reported outcome instruments that accurately measure psychosocial distress. 9,2325 …”
Section: Introductionmentioning
confidence: 99%
“…22 Recently, great attention has been paid to developing standardized clinician-reported and patient-reported outcome instruments that accurately measure psychosocial distress. 9,2325 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our article outlines a process that began in early 2011, first as a UK-wide endeavor and later as part of the Global Task Force for Holistic Outcomes, an initiative of the American Cleft Palate-Craniofacial Association (ACPA). The article also follows an earlier publication (Stock et al, 2016) in which we describe the process for achieving consensus in the measurement of psychological adjustment at age 0 to 7 years. At the time of the 2017 The International Consortium for Health Outcomes Measurement (ICHOM) publication (Allori et al, 2017), we were nearing the conclusion of our work in this area.…”
mentioning
confidence: 99%